Wine complex of the Republik of Moldova and some aspects of the Covid-10 pandemic - Svetlana Fedorchukova; Boris Gaina; Galina Kobirman (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The coronavirus pandemic has made its own adjustments in all sectors of the national economy and in the social sphere. This year's drought has also negatively impacted the agricultural sector. Viticulture and winemaking, being strategic sectors of the national economy, suffered heavy losses. The aim of this work is to study the changes in the wine-making complex of the Republic of Moldova under the influence of the pandemic and other related factors. As information sources we used the information obtained from the National Office of Vine and Wine, Ministry of Agriculture, Regional Development and Environment, National Statistics Center of the Republic of Moldova, Academy of Sciences of Moldova , the daily "Logos press". As working methods were used: systemic data analysis; their mathematical-statistical processing; determining the multiple socio-economic indices that characterize the actuality of the wine complex of RM. The main results of the researches: The COVID-19 pandemic has closed practically all social entities, which sell tangible quantities of domestic wines and spirits on the domestic market; The reserves-stocks of 18 million dal of quality wines from the 2019 harvest, currently existing in the country, will satisfy the export demand in the amount of 100%; Among the existing reserves in the increase of sales of high quality wines, remarkable is the online trade, both on the domestic market, but especially on the international one.
Keywords: Q13; 330; wine; vine; harvest; consumption; winery; local market; profit